Communication Ambassadors—an Australian Social Media Initiative to Develop Communication Skills in Early Career Scientists - Jack T. H. Wang (American Society for Microbiology, 2018)
Science communication is a skill set to be developed through ongoing interactions with different stakeholders across a variety of platforms. Opportunities to engage the general public are typically reserved for senior scientists, but the use of social media in science communication allows all scientists to instantaneously disseminate their findings and interact with online users. The Communication Ambassador program is a social media initiative launched by the Australian Society for Microbiology to expand the online presence and science communication portfolios of early-career scientists. Through their participation in the program, a rotating roster of Australian microbiologists have broadened the online reach of the Society’s social media channels as well as their own professional networks by attending and live-tweeting microbiology events throughout the year. We present the Communication Ambassador program as a case study of coordinated social media activity in science communication to the general public, and describe the potential for its applications in science education and training.